Recessive distal renal tubular acidosis in Sarawak caused by AE1 mutations - Keng, E. Choo; Taija, K. Nicoli; Lesle, J. Bruce; Tanner, Michael J. A.; Ruiz-Linares, Andres; Wrong, Oliver M. (Springer, 2006)
Mutations of the AE1 (SLC4A1, Anion-Exchanger 1) gene that codes for band 3, the renal and red cell anion exchanger, are responsible for many cases of familial distal renal tubular acidosis (dRTA). In Southeast Asia this disease is usually recessive, caused either by homozygosity of a single AE1 mutation or by compound heterozygosity of two different AE1 mutations. We describe two unrelated boys in Sarawak with dRTA associated with compound heterozygosity of AE1 mutations. Both had Southeast Asian ovalocytosis (SAO), a morphological abnormality of red cells caused by a deletion of band 3 residues 400–408. In addition, one boy had a DNA sequence abnormality of band 3 residue (G701D), which has been reported from elsewhere in Southeast Asia. The other boy had the novel sequence abnormality of band 3 (Q759H) and profound hemolytic anemia.